1993
DOI: 10.1152/jappl.1993.75.6.2429
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension of heart rate time series: an effective measure of autonomic function

Abstract: Previous studies suggested that heart rate (HR) time series may be more appropriately analyzed by nonlinear techniques because of the nonlinear nature of these data. In this study, we quantified the complexity of the HR time series, using fractal dimension, a previously described measure developed to study axonal growth, which quantifies the space-filling propensity and convolutedness of a waveform, and compared these results with another recently used measure, approximate entropy. Fractal dimension and approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
3
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 0 publications
9
48
3
1
Order By: Relevance
“…We observed a marked reduction of sample entropy with the change of position from supine to standing, which is in agreement with observations by Yeragani et al (25). This fact indicates the simplification of heart rate control in standing with predominance of LF rhythm after reduction of vagal influences on the heart following parasympathetic withdrawal and sympathetic activation (25).…”
Section: Autonomic Nervous System Hrv and Exercisesupporting
confidence: 92%
See 1 more Smart Citation
“…We observed a marked reduction of sample entropy with the change of position from supine to standing, which is in agreement with observations by Yeragani et al (25). This fact indicates the simplification of heart rate control in standing with predominance of LF rhythm after reduction of vagal influences on the heart following parasympathetic withdrawal and sympathetic activation (25).…”
Section: Autonomic Nervous System Hrv and Exercisesupporting
confidence: 92%
“…This fact indicates the simplification of heart rate control in standing with predominance of LF rhythm after reduction of vagal influences on the heart following parasympathetic withdrawal and sympathetic activation (25). During post-exercise recovery sample entropy was slightly decreased compared to supine rest before exercise and regained supine rest values after 30 min.…”
Section: Autonomic Nervous System Hrv and Exercisementioning
confidence: 89%
“…In our previous reports, we found that approximate entropy (APEN) and fractal dimension (FD), using the method of Katz (1988), correlated highly significantly with each other and also with the HF power on spectral analysis (Yeragani et al, 1993b(Yeragani et al, , 1997. Unlike these measures, MED, LLE and NL measures had no substantial correlation with any of the time-domain measures (Radhakrishna et al, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…We have previously used a similar technique to perform band analysis of the signal using FD and APEN (Yeragani et al, 1993b). We attempted to compare how each of these bands contributes toward the non-linearity and chaos of the UF time series.…”
Section: Filtering Of the Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation